2004
DOI: 10.1038/sj.emboj.7600142
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for host recognition by the Haemophilus influenzae Hia autotransporter

Abstract: Haemophilus influenzae is an important human pathogen that initiates infection by colonizing the upper respiratory tract. The H. influenzae Hia autotransporter is an adhesive protein that promotes adherence to respiratory epithelial cells. Hia adhesive activity resides in two homologous binding domains, called HiaBD1 and HiaBD2. These domains interact with the same host cell receptor, but bind with different affinities. In this report, we describe the crystal structure of the high-affinity HiaBD1 binding domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(108 citation statements)
references
References 32 publications
4
103
1
Order By: Relevance
“…2) (263). Recent structural investigations have demonstrated that the H. influenzae Hia adhesin is a trimeric protein secreted in a manner analogous to YadA rather than the true autotransporters, as previously described (465,474,541). This type of trimeric conformation and mode of secretion has been proposed as an alternative model for autotransporter secretion system (see above) and has been designated the type Vc or AT-2 pathway (Fig.…”
Section: Type Vcmentioning
confidence: 99%
“…2) (263). Recent structural investigations have demonstrated that the H. influenzae Hia adhesin is a trimeric protein secreted in a manner analogous to YadA rather than the true autotransporters, as previously described (465,474,541). This type of trimeric conformation and mode of secretion has been proposed as an alternative model for autotransporter secretion system (see above) and has been designated the type Vc or AT-2 pathway (Fig.…”
Section: Type Vcmentioning
confidence: 99%
“…This fragment was digested with EcoRI and BamHI and then ligated to EcoRI/ BamHI-digested pGEX-6P-1 (GE Healthcare, Piscataway, NJ), generating pGEX::Cha70-473, which was transformed into E. coli DH5␣. Cultures of DH5␣/pGEX::Cha70-473 were incubated at 37°C to an optical density of 0.4 to 0.5, and then expression of the glutathione S-transferase (GST)-Cha fusion protein was induced with 0.1 mM isopropyl-␤-D thiogalactopyranoside at 30°C for 4 h. Purification of the GST-Cha protein was performed as described previously, with minor modifications (53). Briefly, cells were harvested and lysed by sonication in lysis buffer (5 mM EDTA and 1 mM Pefabloc SC [Roche] in phosphate-buffered saline, pH 7.4), and the protein was isolated from clarified supernatant by affinity chromatography with glutathione-Sepharose beads (Pierce) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Hia is an autotransporter that mediates adherence to cultured epithelial cells via two distinct binding domains contained within residues 50-252 and 580-714, and it has a translocator domain contained within residues 1,023-1,098 (40)(41)(42)(43). Whole-cell sonicates and trichloroacetic acid-precipitated supernatant proteins generated from DH5␣ expressing either Hia or the HMW1-Hia chimeric protein in the presence of HMW1B were examined by immunoblot analysis.…”
Section: Hmw1b Interacts With the N-terminal Fragment Of Hmw1mentioning
confidence: 99%